Grounds for the establishment of a state-owned resort on the territory of the city of Morshyn, Lviv region, Ukraine - Babov, Konstantin; Nikipelova, Olena; Sydorenko, Olha; Gushcha, Sergey; Zabolotna, Irina; Zukow, Walery (Ecological Questions, 2020)
For the organization of the resorts are environmentally friendly natural areas of resorts, which have natural therapeutic and recreational resources, which is a powerful potential for the development of medical rehabilitation, treatment, health improvement and medical tourism are used. The creation of resorts requires the presence of a number of components: assessment of the environmental component natural therapeutic resources, sanatorium and health resorts, infrastructure (balneological, mud therapy, pump room with mineral water, etc.) and a professional staff of employees. Depending on the quality and value of natural therapeutic resources, there are distinct state and local resorts. On the territory of the city of Morshyn (Lviv region, Ukraine), almost 150 years ago, the use of mineral water for treatment was applied for the first time. Low anthropogenic impact on the environmental status of Morshyn has been established. During the period of independence of Ukraine, the medical-biological evaluation of the medical brines of the Morshynsky deposit of Bonifaci, Banya and Ninivsky deposits was carried out, which included ecological, geographical, hydro-geological, physico-chemical, microbiological and experimental studies in laboratory animals and clinical trials. Also, the current state of the natural territories and infrastructure of the sanatorium and resort establishments is evaluated, the definition of the natural territories of the city of Morshyn grounded as a resort of state importance. At the same time, one of the main conditions justifying the designation of the territory of Morshyn as a resort of state importance is its definition - as an environmentally friendly destination.